Tendencias acerca del concepto de los espacios educativos - Caballero García, María Encarnación (2022)
The conception of educational spaces is generated within a technological society eager to prepare students. It is proposed to discover what concepts are considered about educational spaces creating trends. The literature review methodology considers the WOS database, selecting and critically reviewing 10 current publications. It is concluded that there is a profusion of new concepts that are considered the assimilation of these new spaces, the learning spaces and the technologies used. Themes are also considered, considering the situation of students and teachers, adapting to these new spaces.